2002
DOI: 10.1108/09526860210448492
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ perceptions of breaking bad news

Abstract: The growth of the “patient‐centred” approach to health care has highlighted the importance of quality communication practices. One area that remains problematic, however, is the process of breaking bad news to patients and/or relatives. Hence, there have been calls for more research and training in this domain. Reports the findings of a study that used the critical incident technique to explore the breaking bad news encounter from the perspective of the health care practitioner. In total 33 senior medical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
7
0
9
Order By: Relevance
“…They have been used in communication skills training in medical school for a number of years, and extensive research has established that these sessions are both credible and reliable. 7 Furthermore, studies have demonstrated that evaluation of trainees' communication and interpersonal skills by such actors provides a reasonable proxy for expected patient satisfaction. 7 This is a potentially beneficial feature of using standardized patients, since it is not only training in, but also evaluation of, interpersonal and communication skills that has been mandated for inclusion into residency program curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been used in communication skills training in medical school for a number of years, and extensive research has established that these sessions are both credible and reliable. 7 Furthermore, studies have demonstrated that evaluation of trainees' communication and interpersonal skills by such actors provides a reasonable proxy for expected patient satisfaction. 7 This is a potentially beneficial feature of using standardized patients, since it is not only training in, but also evaluation of, interpersonal and communication skills that has been mandated for inclusion into residency program curricula.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is, however, overwhelming evidence that communication skills can be effectively taught and learned 6 and that better communication leads to improved patient outcomes. 7 Effective communication is especially important in situations requiring the breaking of bad news to patients. There is abundant literature demonstrating the sensitive nature and importance of effective conveyance of bad news to patients, 7 but this topic has almost exclusively been examined in the general medical and surgical subspecialties, and has generally centered on cancer patients or those who are terminally ill. [8][9][10][11] There are only 2 articles 12,13 in the literature that specifically address the issue of communication skills in the field of ophthalmology; however, both describe the potential for improving ophthalmologists' communication skills in general and do not broach the topic of breaking bad news.…”
mentioning
confidence: 99%
“…Estudos indicam que a maioria dos profissionais da equipe de saúde sente-se incomodada e relativamente despreparada para este momento (17,18) , destacando a importância do desenvolvimento de treinamento para essa comunicação (13,17,19,20) .…”
Section: Revelar Ou Não a Verdade Do Diagnósticounclassified
“…A escolha do ambiente na comunicação do diagnóstico vem sendo evidenciada em alguns estudos que sugerem a escolha de um local quieto e tranqüilo, com privacidade e conforto (6) , com arranjos físicos que permitam uma distância interpessoal adequada, entre outros (20,33,34) .…”
Section: Local E Duração Da Comunicaçãounclassified
“…Dickson et al (2002) defendem que a forma de comunicação de uma má notícia continua sendo um problema aos pacientes e parentes; portanto, exige mais pesquisas e treinamento dos profissionais para dominar o assunto.Conforme os resultados do estudo mostram, e a literatura aponta, urge que se incluam nos currículos dos cursos de graduação e pós-graduação das profissões médica e de enfermagem disciplinas que abordem o conteúdo sobre comunicação verbal e não-verbal, especialmente, no tocante a situações difíceis, quando é necessário comunicar o diagnóstico de doenças que comprometem a qualidade de vida ou o tempo de vida do paciente. Comunicar o nascimento de um bebê com malformação desfigurante e estabelecer uma assistência ao binômio mãe e filho no contexto da sala de parto confronta os profissionais, no caso, o enfermeiro, a ter de lidar com o desconhecido e o inusitado sem o devido preparo profissional, o que gera angústia e estresse aos profissionais.…”
unclassified